The Differences in Students' Creative Problem-Solving Ability with and without Realistic Mathematics Comic Video - Sipayung, Tetty Natalia; Imelda, Imelda; Siswono, Tatag Yuli Eko; Masriyah, Masriyah (International Journal of Elementary Education, 2021)
Mathematics achievement of students in Indonesia is still lower than students in other countries. It is because the creative ability of students is still low. This study aimed to analyze students' creative problem-solving abilities after using realistic math comics videos. This type of research is quantitative research. A quasi-experimental study with a pretest-posttest comparison design was conducted in this study. The population of this study were all seventh-grade students of SMP, which consisted of four parallel classes. The sample was selected using a random sampling technique so that there were two classes of research samples, namely the control class sample and the experimental class sample. This study used a pretest and posttest instrument for creative problem-solving abilities. In this study, the pretest and posttest score data were normally distributed and homogeneous. Based on the research data analysis using the independent sample t-test, it was concluded that there were differences in the creative problem-solving abilities of students who were taught using real math comics videos with groups of students who were taught not to use fundamental math comics videos. So, it can be concluded that the creative problem-solving abilities of students who are taught using real math comic videos are better than those who are not taught using real math comic videos.